Response of glufosinate‐resistant canola to late applications of glufosinate. Issue 3 (2nd September 2016) - Tozzi, E.; Willenborg, C.J.; Harker, K.N.; O'Donovan, J.T.; Blackshaw, R.E.; Strelkov, S.E.
Abstract : The objectives of this study were to characterize the effects of glufosinate application timing on glufosinate‐resistant canola growth, yield, and yield components. Earn 0.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/774 .